Substrate Selection of Ascidian Larva: Wettability and Nano-Structures - Euichi Hirose; Noburu Sensui (Journal of Marine Science and Engineering, 2021)
Ascidians are marine sessile chordates that comprise one of the major benthic animal groups in marine ecosystems. They sometimes cause biofouling problems on artificial structures underwater, and non-indigenous, invasive ascidian species can potentially and seriously alter native faunal communities. Ascidian larvae are usually tadpole-shaped, negatively phototactic, and adhere on substrates by secreting a glue from their adhesive organs. Although larvae often prefer hydrophobic surfaces, such as a silicone rubber, for settlement, hydrophobic materials are often used to reduce occurrence of fouling organisms on artificial structures. This inconsistency may indicate that an attractive surface for larvae is not always suitable for settlement. Micro-scale structures or roughness may enhance the settlement of ascidian larvae, but settlement is significantly reduced by a nano-scale nipple array (or moth-eye structure), suggesting functional properties of similar structures found on the body surfaces of various invertebrates. The substrate preferences of larvae should be one of the important bases in considering measures against biofouling, and this review also discusses the potential uses of materials to safely reduce the impacts of invasive species.